Early‐onset Preeclampsia in Lupus Pregnancy. Issue 1 (12th December 2016) - Simard, Julia F.; Arkema, Elizabeth V.; Nguyen, Cathina; Svenungsson, Elisabet; Wikström, Anna‐Karin; Palmsten, Kristin; Salmon, Jane E.
Abstract: Background: Systemic lupus erythematosus (SLE) is a chronic systemic autoimmune disease that occurs during childbearing years and has been associated with preeclampsia. However, little is known about preeclampsia of early onset, which is associated with severe adverse maternal and perinatal outcomes. Methods: Using national population‐based Swedish registers we identified women with SLE (≥2 visits with corresponding ICD codes) and a sample without SLE who gave birth to singleton infants 2001–12. Risk ratios (RR) and 95% confidence intervals (CI) for early‐onset preeclampsia (defined by ICD codes corresponding to preeclampsia registered at <34 weeks) in SLE women were calculated based on adjusted modified Poisson models for first, subsequent, and all pregnancies. Result: Among 742 births to women with SLE and 10 484 births to non‐SLE women, there were 32 (4.3%) and 55 (0.5%) diagnoses of early‐onset preeclampsia respectively. SLE was associated with an increased risk of early‐onset preeclampsia (RR 7.8, 95% CI 4.8, 12.9, all pregnancies). The association remained similar upon restriction to women without pregestational hypertension. Adjustment for antiphospholipid syndrome (APS)‐proxy attenuated the association. RRs for early‐onset preeclampsia were smaller for subsequent pregnancies (RR 4.7, 95% CI 2.0, 11.2) compared to first and all (see above). Conclusion: Women with SLE are at increased risk of early‐onset preeclampsia and this increased risk may be independent of the traditional risk factors such as pregestational hypertension, APS, BMI, or smoking. Women with SLE during pregnancy should be closely monitored for early‐onset preeclampsia and future research needs to identify the non‐traditional preeclampsia factors that might cause this serious outcome.